2017
DOI: 10.1001/jamaoto.2016.2988
|View full text |Cite
|
Sign up to set email alerts
|

Association of Recurrence of Infected Congenital Preauricular Cysts Following Incision and Drainage vs Fine-Needle Aspiration or Antibiotic Treatment

Abstract: Among infants and children undergoing excision of preauricular cysts, a history of infection was not associated with a higher recurrence rate. There was, however, evidence to suggest that a higher rate of recurrence exists among children who had a preoperative history of infection treated with I & D. Our results suggest a more conservative treatment of infected preauricular pit and/or sinus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…However, studies have shown that repeated sinus infectious process produces fibrotic and edematous changes which may distort the normal tissue structure and sinus tract making definitive surgery more difficult thereby leaving squamous epithelium behind to cause recurrence. 11 Staphylococcus aureus was the commonest isolated organism in 9 (53%) of the 17 patients in our study while the culture of the discharge in 5 (29.4%) patients yielded no significant growth after 48 hours incubation. This may be attributed to indiscrimate use of antibiotics in selfmedication before presenting to a specialist for proper treatment.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…However, studies have shown that repeated sinus infectious process produces fibrotic and edematous changes which may distort the normal tissue structure and sinus tract making definitive surgery more difficult thereby leaving squamous epithelium behind to cause recurrence. 11 Staphylococcus aureus was the commonest isolated organism in 9 (53%) of the 17 patients in our study while the culture of the discharge in 5 (29.4%) patients yielded no significant growth after 48 hours incubation. This may be attributed to indiscrimate use of antibiotics in selfmedication before presenting to a specialist for proper treatment.…”
Section: Discussionmentioning
confidence: 54%
“…This may be attributed to indiscrimate use of antibiotics in selfmedication before presenting to a specialist for proper treatment. 7,11 None of the patients had associated congenital anomalies such as hearing or renal impairments. 1,2 Complete wide local surgical excision of the preauricular sinus tract were all squamous epithelium are removed is the gold standard of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The structure presents as a simple epithelial invagination into the auricular stroma and can often become inflamed, leading to discharge from the superficial opening and discomfort [ 1 , 7 ]. This itself can lead to serious complications, such as facial paralysis, due to its location near the facial nerve [ 1 , 7 , 8 ]. Clinical history in such cases is important to distinguish between a fistulized abscess and an inflamed PAuS.…”
Section: Introductionmentioning
confidence: 99%
“…Rarely, however, similar structures can be located in other areas of the auricle such as the tragus, pinna, etc. due to the complexity of auricular formation (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…However, as a structure identified as a part of a number of inherited syndromes, such as the Beckwith-Wiedemann syndrome, Lachiewicz-Sibley and the brachio-oto-renal syndrome also known as Melnik-Fraser, there is very little modern evidence and information on the mechanisms of the individual transgenerational inheritance or lack thereof for PAuS (6,7,11,13,(20)(21)(22). Most of the research in the field, especially in the genetic and genealogical aspects, had been carried out prior to the 1950s and, to our knowledge, no similar studies have been carried out ever since (23)(24)(25)(26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%